(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
The objective of the study was to explore the seasonal variations in the water of Buriganga River with respect to heavy metals contamination. Water samples were collected six times with an interval of two months starting from June 2010 to April 2011. Collection of samples started at the point of 90o20´12"E and 23o46´25"N, continued towards downstream at an interval of 1 km upto 26 km by using GPS and ended at the point of 90o27’36"E and 23o37’50"N. The spatial database of the collected water samples were built with ARCGIS 9.3.1 as the platform of case study of Buriganga River. Six trace metals viz. cadmium (Cd), iron (Fe), zinc (Zn), chromium (Cr), copper (Cu) and lead (Pb) were analyzed for water from each sampling points to examine the level of contamination whether it exceed or within the permissible limit. The concentrations of trace metals in water samples were determined using atomic absorption spectrophotometer. The concentration range of these trace metals were found 0 to 0.01 mg/L for Cd, 0.46 to 1.19 mg/L for Fe, 0 to 0.38 mg/L for Zn, 0 to 0.074 mg/L for Cu, 0 to 0.098 mg/L for Cr and 0 to 0.074 mg/L for Pb. The study suggested that, concentration of Fe, Cr and Cd in river water were increased during dry season and in some points near Hazaribagh, Zinzira and Sadarghat it crossed the maximum permissible limit for drinking water purposes and irrigation water supply. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10712 Bangladesh J. Sci. Ind. Res. 47(1), 9-18, 2012